Studies of the Fusibility of Coal Ash - Quilao, T. A.; Balais, W. A.; Abarquez, F. I.; Bion, H. H.; Magpantay, C. G.; Vinluan, F. D.; Yamada, K.; Tsurue, T.; Takeda, S.; Ishizaki|, K. (Philippine Engineering Journal; Vol 16 No 1 (1995), 2021)
A study, which aims to develop a technology for the preparations of a high quality absorbent for Soᵪ using coal ash to control air pollution caused by coal-fired thermal power plants in the Philippines, is currently being jointly undertaken by ITDI and HNIRI. During its first year if implementation, the physical, chemical and thermal characteristics of Philippine and Japanese coal ash samples were determined. Results show that Philippine coals as samples are of the silicoaluminous type while that of the Japanese coal samples are of the aluminosiliceous type. Three (3) common major elements, namely, quartz, mullite and hematite are found in all coal ash samples. A correlation between the melting point and chemical composition of the coal ash samples shows that the coal ash samples having a low acid-base index resulted in high melting points.